2D multichannel seismic reflection stacked data (GI Gun) of RV SONNE cruise SO232 in 2014 to the Agulhas Plateau, seismic reflection profile AWI-20140232 - Uenzelmann-Neben, Gabriele (PANGAEA, 2025)
Seismic reflection data collected in the Agulhas Plateau during cruise SO232 with RV Sonne in 2014. 2 GI-guns were used a seismic source, the data were recorded with a 3000 m (active length) long digital streamer. The data are unprocessed. No gain, filter or mute have been applied. The data are in SEGY format. See cruise report (Uenzelmann-Neben, 2014) or ReadMe file for more information on acquisition parameters.
Keywords: AWI Geophysics; Mozambique Ridge; Seismic reflection data